Modulating molecular interactions in pea protein to improve its functional properties - Yanting Shen; Zhenjiao Du; Xiaorong Wu; Yonghui Li (Journal of Agriculture and Food Research, 2022)
Proteins exist in numerous spatial arrangements and are stabilized by various inter- and intra-molecular forces. The objectives of this study were to investigate the functional properties of pea protein isolate in terms of water/oil holding capacity, emulsifying and foaming properties, solubility, and gelation by modulating protein covalent and non-covalent interactions with specific denaturants/modifiers and to understand the physicochemical characteristics (e.g., free amino group content, free sulfhydryl group content, surface hydrophobicity, SDS-PAGE profile, secondary structures) of the unfolded pea proteins that are responsible for the functional changes. All the denatured proteins possessed significantly increased solubility. Both urea and SDS unfolded proteins had significantly higher water holding capacity and oil holding capacity of up to 5.01 and 5.09 g H2O/g, and 3.06 and 2.84 g oil/g compared with the control pea protein (4.12 g H2O/g and 1.29 g oil/g), respectively. The proteins unfolded with urea or SDS also showed improved emulsification properties. The trypsin hydrolyzed protein exhibited the highest foaming capacity and better gelation properties among all the treatments. Principal component analysis indicated strong associations between protein functional and physicochemical properties and molecular interactions. This study provides useful fundamental knowledge in tailoring protein structures in order to enhance its functionalities and broaden the food applications.